(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study investigated the effectiveness of the traditional "dodge ball" game in improving underhand passing accuracy and control among elementary school volleyball players, hypothesising a significant positive influence. A quantitative pre-experimental design with a one-group pretest-posttest model was applied to 23 students from SD Negeri Parakanmuncang II’s extracurricular volleyball program, selected via total sampling. Underhand passing skills were measured using a wall-passing accuracy test. Data collection involved a pretest, eight sessions of a modified "dodge ball" game where defenders used underhand passing to block thrown balls, and a posttest. Data was analyzed using SPSS 26.0, including Shapiro-Wilk normality, Paired Sample t-test, and R-Square regression analysis. Results indicated that both pretest (Sig. 0.381) and posttest (Sig. 0.383) data were normally distributed. The t-test showed a significant difference between pretest and posttest scores (Sig. 0.000, t = -6.442), with average scores increasing from 4-11 to 6-14. The R-Square value of 0.413 confirmed that the modified game explained 41.3% of the variation in underhand passing improvement. These findings suggest that incorporating modified "dodge ball" games effectively enhances underhand passing skills in elementary school students by providing an engaging and collaborative learning environment, fostering motor, cognitive, and affective development.